Державна регіональна політика у сфері безпеки дорожнього руху: поняття та зміст - Стрижак, А. О.; Stryzhak, A. O. (Науковий вісник публічного та приватного права. - 2023. - Вип. 5. - С. 218-223, 2023)
З’ясовано зміст державної регіональної політики у сфері безпеки дорожнього руху. Стверджено, що державна регіональна політика у сфері безпеки дорожнього руху становить собою окремий об’єкт адміністративно-правого регулювання та становить відповідну складову державної політики, що безпосередньо включає напрям (стратегію) розвитку відносин у сфері забезпечення безпеки дорожнього руху та сукупність адміністративно-правових інструментів реалізації заходів спрямованих на убезпечення порушень норм чинного законодавства у досліджуємій суспільних відносин нормами адміністративного законодавства. Виокремлено ознаки адміністративно-правових відносин, які мають місце під час реалізації державної регіональної політики у сфері безпеки дорожнього руху.

Scientific articles clarify the content of the state regional policy in the field of road safety. The analysis of the scientific positions of scientists and the direct consideration of normative legal acts made it possible to assert that the state regional policy in the field of road traffic safety is a separate object of administrative and legal regulation and is a relevant component of state policy, which directly includes the direction (strategy) of development relations in the field of ensuring road traffic safety and a set of administrative and legal tools for the implementation of measures aimed at ensuring violations of the norms of current legislation in the researched public relations norms of administrative legislation. The signs of administrative-legal relations that take place during the implementation of the state regional policy in the field of road safety are highlighted, namely: 1) they are public-law, since the subject of regulation is relations in the sphere of realization of public (state, public) interests; 2) take place in the field of ensuring road traffic safety; 3) regulated, as a rule, by the norms of administrative legislation; 4) a wide range of subjects of formation and implementation of state regional policy in the field of ensuring road traffic safety; 5) unification aimed at reducing the level of accidents and deaths on the roads, as well as the development of transport infrastructure, etc. It is emphasized that the implementation of the state regional policy in the field of road safety is aimed at the formation of awareness among road traffic participants (subjects) of compliance and enforcement of discipline, as well as a preventive focus on preventing violations of established rules in the field of road safety through the prism of educational activities by appropriate bodies and divisions.

Определено содержание государственной региональной политики в области обеспечения безопасности дорожного движения. Выделены особенности административно-правовых отношений, имеющих место при реализации государственной региональной политики в области обеспечения безопасности дорожного движения.
State regional policy in the field of road safety: concept and content
Keywords: державна політика; державна регіональна політика; сфера безпеки дорожнього руху; адміністративне законодавство; учасники суспільних відносин; state policy; state regional policy; road safety; administrative legislation; participants in public relations; государственная политика; государственная региональная политика; сфера безопасности дорожного движения; административное законодательство; участники социальных отношений